2004
DOI: 10.1002/jcb.20073
|View full text |Cite
|
Sign up to set email alerts
|

β‐Carotene storage, conversion to retinoic acid, and induction of the lipocyte phenotype in hepatic stellate cells

Abstract: Hepatic stellate cells (HSCs) are the major site of retinol (ROH) metabolism and storage. GRX is a permanent murine myofibroblastic cell line, derived from HSCs, which can be induced to display the fat-storing phenotype by treatment with retinoids. Little is known about hepatic or serum homeostasis of beta-carotene and retinoic acid (RA), although the direct biogenesis of RA from beta-carotene has been described in enterocytes. The aim of this study was to identify the uptake, metabolism, storage, and release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Indeed, some nonintestinal viral infections also induce 4 7 + T cells 103 and there may be constitutive sources of RA in the lung mucosa 104 and liver. 105 Also, it remains to be determined whether RA synthesis can be induced in nonintestinal tissues under inflammatory or infectious conditions and whether there are additional RA-independent mechanisms of gut-homing imprinting. 106 It is also unknown how IgA-ASCs are imprinted to home to mucosal compartments other than the small bowel.…”
Section: Mechanisms Of Imprinting Of Gut-homing B Cells and Ascmentioning
confidence: 99%
“…Indeed, some nonintestinal viral infections also induce 4 7 + T cells 103 and there may be constitutive sources of RA in the lung mucosa 104 and liver. 105 Also, it remains to be determined whether RA synthesis can be induced in nonintestinal tissues under inflammatory or infectious conditions and whether there are additional RA-independent mechanisms of gut-homing imprinting. 106 It is also unknown how IgA-ASCs are imprinted to home to mucosal compartments other than the small bowel.…”
Section: Mechanisms Of Imprinting Of Gut-homing B Cells and Ascmentioning
confidence: 99%
“…Activated HSCs respond to exogenous retinoids in culture (Hellemans et al 2004;Martucci et al 2004;Vogel et al 2000). Studies have shown that supplementation of cultured HSCs with ATROH prevents the activation of HSCs, inhibits transdifferentiation, and promotes the lipofibroblastic vitamin-A-storing phenotype (Vogel et al 2000;Fortuna et al 2003;Hellemans et al 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Along with retinoid stores, liver has also been shown to accumulate significant amount of carotenoids under normal physiological conditions. In vivo and in vitro models have shown that both hepatocytes and hepatic stellate cells accumulate carotenoid [1921]. Hepatic accumulation of β-carotene has been observed in both the BCO1 and BCO2 -deficient mice [22,23].…”
Section: Introductionmentioning
confidence: 99%